(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The personal care products are discovered and used in the ancient world. Each country has their own history of personal care products. In ancient India, sixteen methods of self-beautification were practiced which are popularly known as SolahShringar. The personal care category in India was valued at Rs. 54.6 billion. An average Indian spends 8% of his income on personal care products. Personal care mainly consists of Hair Care, Skin Care, Oral Care, Personal Wash (Soaps), Cosmetic and Toiletries, Feminine Hygiene. India’s personal care industry is composed of hair care, bath products, skin care and cosmetics, and oral care. The sector is driven by rising income, rapid urbanization, and celebrity promotions. This industry accounts for 22% of the country’s fast-moving consumer goods (FMCG), which is the term for Consumer Packaged Goods in India